Design and Development of Econoplay Based PowerPoint Media For Teaching on Market and Price Formation Concepts - Fiolisa Adinda Putri Karniawan; Nur Anita Yunikawati (Jurnal Inovasi Pendidikan Ekonomi, 2025)
Technological advances in education demandinnovation in learning media to make it moreinteractive. Observations at SMA Negeri 3 Blitar showthat the method of learning economics is still withconventional lectures and full text PowerPoint, so thatstudent interest and understanding are low. Thisresearch is Econoplay, developing PowerPoint-basedinteractive learning media with animation, video,educational games, and QR-Code evaluation using theADDIE model. The research method is quantitativewith data collection through questionnaires. The resultsshowed that material expert validation obtained 96.6%(very valid), media expert validation 98% (very valid),small group trial 91% (very feasible), and large grouptrial 92%, proving the effectiveness of Econoplay inincreasing students' understanding and interest inlearning. Thus, Econoplay is feasible to use aseconomic learning media in high school.